Investigation of Clinical Safety of Human iPS Cell-Derived Liver Organoid Transplantation to Infantile Patients in Porcine Model. (22nd October 2020) - Tsuchida, Tomonori; Murata, Soichiro; Hasegawa, Shunsuke; Mikami, Satoshi; Enosawa, Shin; Hsu, Huai-Che; Fukuda, Akinari; Okamoto, Satoshi; Mori, Akihiro; Matsuo, Megumi; Kawakatsu, Yumi; Matsunari, Hitomi; et al.
Transplantation of liver organoids has been investigated as a treatment alternative to liver transplantation for chronic liver disease. Transportal approach can be considered as a method of delivering organoids to the liver. It is important to set the allowable organoid amount and verify translocation by intraportal transplantation. We first examined the transplantation tolerance and translocation of porcine fetal liver-derived allogeneic organoids using piglets. Fetal liver-derived organoids generated from the Kusabira Orange-transduced pig were transplanted to the 10-day-old piglet liver through the left branch of the portal vein. All recipients survived without any observable adverse events. In contrast, both local and main portal pressures increased transiently during transplantation. In necropsy samples, Kusabira Orange-positive donor cells were detected primarily in the target lobe of the liver and partly in other areas, including the lungs and brain. As we confirmed the transplantation allowance by porcine fetal liver-derived organoids, we performed intraportal transplantation of human-induced pluripotent stem cell (iPSC)-derived liver organoid, which we plan to use in clinical trials, and portal pressure and translocation were investigated. Human iPSC-derived liver organoids were transplanted into the same 10-day-old piglet. Portal hypertension and translocation of human iPSC-derived liver organoids to the lungs were observed in one of two transplanted animals. Translocation occurred in the piglet in which patent ductus venosus (PDV) was observed. Therefore, a 28-day-old piglet capable of surgically ligating PDV was used, and after the PDV was ligated, human iPSC-derived liver organoids with the amount of which is scheduled in clinical trials were transplanted. This procedure inhibited the translocation of human iPSC-derived liver organoids to extrahepatic sites without no portal hypertension. In conclusion, human iPSC-derived liver organoids can be safely transplanted through the portal vein. Ligation of the ductus venosus prior to transplantation was effective in inhibiting extrahepatic translocation in newborns and infants.